Agility and resilience as antecedents of supply chain performance under moderating effects of organizational culture within the humanitarian setting: a dynamic capability view. Issue 14 (26th October 2018) - Altay, Nezih; Gunasekaran, Angappa; Dubey, Rameshwar; Childe, Stephen J.
Abstract: This study examines the effects of supply chain agility (SCAG) and supply chain resilience (SCRES) on performance under the moderating effect of organizational culture. We have used the dynamic capability view (DCV) to conceptualize our theoretical models for different phases of humanitarian supply chain (HSC) (pre and post-disaster phases). We used partial least squares (PLS) to examine the proposed research hypotheses using 335 responses gathered from organizations in India using questionnaires designed for a single respondent. The results suggest that SCAG and SCRES are two important dynamic capabilities of supply chain, have significant effects on pre-disaster performance (PRE-DP). The control orientation does not have significant effect on the path joining SCAG and PRE-DP. However, the control orientation has a significant interaction effect on the path joining SCRES and PRE-DP. Similarly, SCRES has significant effect on post-disaster performance (POST-DP) but SCAG has no significant effect on POST-DP. In contrast, the flexible orientation has significant moderation effects on the paths SCAG/SCRES and POST-DP. These findings contribute to our understanding of the differential effect of SCAG/SCRES on supply chain performance in different contexts. The results provide further understanding to develop appropriate strategies for different phases. Finally, limitations of our study and future research are presented.